The Impact of the COVID-19 Pandemic on People With Cognitive Impairment Residing in Aged Care Facilities: An Integrative Review - Samantha Battams PhD; Angelita Martini PhD (SAGE Publishing, 2023)
This review explored the impact of the COVID-19 pandemic on people with cognitive impairment living in aged care facilities. It also considered policy and organizational responses to COVID-19, and makes recommendations to ameliorate the impact of the pandemic on residents with cognitive impairment in aged care facilities. ProQuest, PubMed, CINAHL, Google Scholar, and Cochrane Central were searched April-May 2022 for peer reviewed articles, and an integrative review of reviews was conducted. Nineteen reviews were identified which referred to people with cognitive impairment living in residential aged care facilities (RACFs) during COVID-19. Negative impacts were highlighted, including COVID-19 related morbidity and mortality, social isolation, and cognitive, mental health and physical decline. Few research articles and policy responses consider people with cognitive impairment in residential aged care. Reviews highlighted that social engagement of residents should be better enabled to reduce the impact of COVID-19. However, residents with cognitive impairment may have inequitable access to communications technology for the purposes of assessment, health care and social engagement, and require more support (along with their families) to access this technology. Greater investment in the residential aged care sector (eg, for workforce and training) is required to address the significant impacts of the COVID-19 pandemic on people with cognitive impairment.